2010
DOI: 10.1095/biolreprod.109.079335
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive WNT/Beta-Catenin Signaling in Murine Sertoli Cells Disrupts Their Differentiation and Ability to Support Spermatogenesis1

Abstract: Sertoli and germ cell interactions are essential for spermatogenesis and, thus, male fertility. Sertoli cells provide a specialized microenvironment for spermatogonial stem cells to divide, allowing both self-renewal and spermatogenesis. In the present study, we used mice with a conditional activated allele of the beta-catenin gene (Ctnnb1(tm1Mmt)(/+)) in Sertoli cells expressing Cre recombinase driven by the anti-Müllerian hormone (AMH; also known as Müllerian-inhibiting substance) type II receptor promoter (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
127
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(154 citation statements)
references
References 59 publications
12
127
3
Order By: Relevance
“…The retained MD tissue was often accompanied by fibrosis near the adjacent tubules, which had the deleterious effect of causing obstructive azoospermia by formation of enlarged epididymal cysts (Fig. 4) of impacted sperm that resemble spermatoceles in most of the mutant mice with what little spermatogenesis was occurring in their testes before seminiferous tubule degeneration begins in Amhr2-Cre;Ctnnb1 Δ(ex3) mice when they are ∼4 wk old (18,19).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The retained MD tissue was often accompanied by fibrosis near the adjacent tubules, which had the deleterious effect of causing obstructive azoospermia by formation of enlarged epididymal cysts (Fig. 4) of impacted sperm that resemble spermatoceles in most of the mutant mice with what little spermatogenesis was occurring in their testes before seminiferous tubule degeneration begins in Amhr2-Cre;Ctnnb1 Δ(ex3) mice when they are ∼4 wk old (18,19).…”
Section: Resultsmentioning
confidence: 99%
“…We and others have also shown that CA β-catenin causes sterility in males by inhibiting postnatal Sertoli maturation and spermatogenesis (18)(19)(20). Given the requirement for Wnt signaling in MD development (21) and the relative paucity of reports linking Wnt signaling and Wolffian duct (WD) differentiation, we examined whether dysregulated β-catenin activity in the adjacent MD mesenchyme affected normal WD development into the epididymis, vas deferens, and seminal vesicles (22,23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It regulates the self-renewal and differentiation of spermatogonial stem cells; however, the balance of self-renewal and differentiation of spermatogonial stem cells is influenced not only by intracellular signals, but also by the microenvironment, termed the spermatogonial stem cell niche, which is formed by surrounding Sertoli cells [76]. By regulating the differentiation and maturation of Sertoli cells, the Wnt signaling pathway has an ability to support spermatogenesis [77]. We found that the transcriptional activity of the Wnt signaling pathway decreases in PN2.…”
Section: Differential Expression Of Genes In Cellular Signaling Pathwaysmentioning
confidence: 99%
“…22 Overexpression of β-catenin leads to uncontrolled proliferation, inhibition of differentiation in Sertoli cells and their function to support germ cells in mice. 23 As a result, relationship of Wnt/β-catenin signaling dysfunction in sertoli, germ cell, and infertility has been confirmed. Leydig cells have not been studied in this regard.…”
mentioning
confidence: 95%